2021
DOI: 10.1039/d1cp03380h
|View full text |Cite
|
Sign up to set email alerts
|

London dispersion dominating diamantane packing in helium nanodroplets

Abstract: Diamantane clusters formed inside superfluid helium nanodroplets were analyzed by time-of-flight mass spectrometry. Distinct cluster sizes were identified as “magic numbers” and the corresponding feasible structures for clusters consisting of...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(19 citation statements)
references
References 63 publications
3
16
0
Order By: Relevance
“…The obtained interaction energies (Table S2, ESI †) for ether clusters CL1-CL3 are in line with our previously obtained values for diamantane clusters 19 and confirm that aggregation of diamondoid ethers in HNDs is indeed an energetically favorable process. As intermolecular LD appears to be the main driving force for the cluster aggregation, increase in cluster size leads to the rise of interaction energies due to multiplication of intermolecular close contacts.…”
Section: Resultssupporting
confidence: 90%
See 4 more Smart Citations
“…The obtained interaction energies (Table S2, ESI †) for ether clusters CL1-CL3 are in line with our previously obtained values for diamantane clusters 19 and confirm that aggregation of diamondoid ethers in HNDs is indeed an energetically favorable process. As intermolecular LD appears to be the main driving force for the cluster aggregation, increase in cluster size leads to the rise of interaction energies due to multiplication of intermolecular close contacts.…”
Section: Resultssupporting
confidence: 90%
“…The choice of the density functional theory (DFT) method was based on our previous benchmarking of similarly bulky molecules in HNDs. 19 We found that the use of Grimme's dispersion correction with Becke-Johnson damping (D3(BJ)), 39,40 the three-body dispersion contributions term implemented in Orca as well as geometrical counterpoise (gCP) correction 43 is desirable in order to account for subtle intermolecular interactions and mitigate the basis-set superposition errors (BSSE), respectively. Zero-point vibrational energy used during the assessment of cluster binding energy was obtained from the semi-empirical quantum mechanical GFN2-xTB method 44,45 at 0.4 K to account for the temperature of the liquid He environment.…”
Section: Theoretical Methodsmentioning
confidence: 99%
See 3 more Smart Citations